Membangun Karakter Berwawasan Luas Melalui Buku Pedoman Pendidikan Karakter Berbasis Permainan Tradisional Pada Anak Usia 10-12 Tahun - Kustika Sari, Christina Dian; Ari Nugrahanta, Gregorius (Universitas Nusantara PGRI Kediri, 2023)
This research aimed to develop a product in the form of perspective (wisdom) character education guidebook based on traditional game for children aged 10-12 years. This research used the Research and Development (R&D) method with the ADDIE type. There were ten certified teachers from Sleman, Bantul, Gunung Kidul, Kulon Progo, Muntilan, Cilacap, Malang, West Kalimantan, and Bali who got involved for the the requirement analysis, ten validators to become judgment experts, and eight children aged 10-12 years who were involved in limited product trials. The results of this study show that 1) The traditional game based character education manual was developed through the ADDIE steps (Analyze, Design, Develop, Implement, and Evaluate, 2) The manual has a score of 3,87 (range 1-4) with